Assessment of primary health care's functions in a health center of buenos aires from the perspective of health proffesionals: cross-sectional study - Segalini, Agustín M.; Weisbrot, Mariela; Vietto, Valeria; Rezzónico, María; Vázquez Peña, Fernando; Terrasa, Sergio; Kopitowski, Karin (Revista del Hospital Italiano de Buenos Aires, 2017)
Primary health care (PHC) favors more efficient and equitable attention to the needs of the population. The objective of this cross-sectional study carried out during 2013 was to evaluate the degree of implementation of the basic functions of PHC in the San Pantaleón Family and Community Medicine Health Center (CMFyCSP), located in Boulogne, San Isidro, Buenos Aires, Argentina, from the perspective of health professionals. The Primary Care Assessment Tool (PCAT) for health professionals validated in Argentina was administered electronically. All professionals with a seniority of at least two years (n = 25) responded the survey. The overall score for essential APS functions was 16.75 SD (1.42) for a maximum of 24 points. Family Focus, Integrality / Rendered Services and Coordination / Information Systems were the functions with the highest scores (3.51 [0.55], 3.49 [0.58], and 3.16 [0.47], respectively
Keywords: Primary Health Care; Community Medicine; Cross-Sectional Studies